Optimization of Stunting Prevention in Communities in Bahliran Village Through the Application Peduli Stunting “Penting” - Bukit, Dhani Syahputra; Sudaryati, Etty; Nainggolan, Pauzi Ibrahim; Arde, Lanova Dwi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting in children must receive attention. This condition can indicate that the child's nutrition is not adequately met. If left untreated, stunting can have long-term impacts on children. The increasingly rapid development of technology affects human life, one of which is the health aspect. This makes it easier to access and disseminate information. The use of technology must be used effectively and efficiently to improve public health. The presence of E-stunting is an implementation of the digitization of child nutrition recording and reporting—an application designed with various features that provide information about stunting. One of the features found in E-stunting is Food Recall. This research aims to solve health problems in Bahliran Village by empowering the community through the stunting care application (Important) to increase community awareness of stunting and Clean and Healthy Living Behavior. This research took eight months, with a research approach method that took three research stages, namely: a) Stage 1. This stage is the initial stage carried out in community empowerment. b) Stage II. In this second stage, there is a transformation of knowledge and skills. In this case, there is a need to learn about various knowledge and skills to support the empowerment activities. c) Stage III. Increased intellectual abilities and skill proficiency. In this activity, the people of Bahliran Village can take advantage of the "IMPORTANT (Stunting Care)" application, which is expected to reduce stunting rates and create a healthy and empowered community.